Effect of Elastomull® elastic bandaging on second-degree burn wound healing in Wistar rats: A preliminary study - Naynuunis Zulfachri; Dedy Syahrizal; Muhsin (Acta Biochimica Indonesiana, 2025)
Background: Second-degree burns are the most common burn injuries, requiring effective wound management to prevent complications. While silver sulfadiazine is the gold standard treatment, the role of elastic bandaging in enhancing healing remains unclear. Objective: To investigate the effectiveness of Elastomull® elastic bandaging combined with silver sulfadiazine in treating second-degree burns in Wistar rats. Methods: Six male Wistar rats were divided into two groups: K(+) group treated with silver sulfadiazine and Elastomull® bandaging, and K(-) group treated with silver sulfadiazine alone. Second-degree burns were induced using a 100°C iron applied for 5 seconds. Wound areas were measured every three days for 18 days and analyzed using Independent-Samples T-Test. Results: The K(+) group consistently showed smaller wound areas from day 3 onwards, with greater total healing (1.87 ± 0.25 cm²) compared to K(-) group (1.03 ± 0.53 cm²). However, differences were not statistically significant (p > 0.05). Conclusion: Elastomull® bandaging showed clinical trends toward improved burn healing but lacked statistical significance, likely due to small sample size. Larger studies are needed to confirm these findings.